Selected Legumes Used As Summer Cover Crops - Jim Rich; David Wright; Jim Marois; Dick Sprenkel (EDIS)
Cover crops are generally planted after a primary (cash) crop for one or more of the following reasons: erosion control, organic matter accumulation, improved soil tilth, pest suppression (weed, disease, nematode, and insect), and nitrogen production. Optimally, a cover crop will provide a wide range of most or all of the previously mentioned benefits, even if the main reason for planting it was more specific. The eight cover/green manure crops described herein have been shown to provide several benefits to a succeeding crop. This document is ENY-688 (IN483), one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Publication Date: August 2003.